Automorphism of the geometry of the group $B_2(2^n)$ as apolynomial mapping - Peykre, L.R.; Пейкре, Л.Р. (Institute of Mathematics, NAS of Ukraine, 1992)
A construction of an automorphism of the geometry of the group $B_2(2^n)$ is given as an extension of an automorphism of a root system. Some properties of the automorphism are proved.